Luminescence of a Transition Metal Complex Inside a Metamaterial Nanocavity. Issue 32 (22nd June 2017) - Connell, Timothy U.; Earl, Stuart K.; Ng, Charlene; Roberts, Ann; Davis, Timothy J.; White, Jonathan M.; Polyzos, Anastasios; Gómez, Daniel E.
Abstract : Modification of the local density of optical states using metallic nanostructures leads to enhancement in the number of emitted quanta and photocatalytic turnover of luminescent materials. In this work, the fabrication of a metamaterial is presented that consists of a nanowire separated from a metallic mirror by a polymer thin film doped with a luminescent organometallic iridium(III) complex. The large spin–orbit coupling of the heavy metal atom results in an excited state with significant magnetic‐dipole character. The nanostructured architecture supports two distinct optical modes and their assignment achieved with the assistance of numerical simulations. The simulations show that one mode is characterized by strong confinement of the electric field and the other by strong confinement of the magnetic field. These modes elicit drastic changes in the emitter's photophysical properties, including dominant nanocavity‐derived modes observable in the emission spectra along with significant increases in emission intensity and the total decay rate. A combination of simulations and momentum‐resolved spectroscopy helps explain the mechanism of the different interactions of each optical mode supported by the metamaterial with the excited state of the emitter. Abstract : The nanocavity of a novel metamaterial that supports several optical modes enables increased luminescence from an organometallic iridium(III) complex, a hybrid magnetic/electric‐dipole emitter. The mechanism for the strong modification to the emission spectrum and spontaneous decay rates is rationalized through analysis of momentum‐ and time‐resolved spectroscopy experiments.